Structure‐Activity Relationship Explorations and Discovery of a Potent Antagonist for the Free Fatty Acid Receptor 2. (12th September 2021) - Højgaard Hansen, Anders; Christensen, Henriette B.; Pandey, Sunil K.; Sergeev, Eugenia; Valentini, Alice; Dunlop, Julia; Dedeo, Domonkos; Fratta, Simone; Hudson, Brian D.; Milligan, Graeme; Ulven, Trond; Rexen Ulven, Elisabeth
Abstract: Free fatty acid receptor 2 (FFA2) is a sensor for short‐chain fatty acids that has been identified as an interesting potential drug target for treatment of metabolic and inflammatory diseases. Although several ligand series are known for the receptor, there is still a need for improved compounds. One of the most potent and frequently used antagonists is the amide‐substituted phenylbutanoic acid known as CATPB (1 ). We here report the structure‐activity relationship exploration of this compound, leading to the identification of homologues with increased potency. The preferred compound 37 (TUG‐1958) was found, besides improved potency, to have high solubility and favorable pharmacokinetic properties. Abstract : Antagonist as the hero : The short‐chain fatty acid receptor FFA2 is a promising drug target for metabolic and inflammatory diseases. Herein we present the SAR exploration of an antagonist series, leading to the discovery of a more potent antagonist with favorable solubility and pharmacokinetic properties.